Analysis of Teaching Quality Factors at Aviation Vocational Education - Suyatmo Suyatmo; Ekohariadi Ekohariadi; Ari Wardhono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The decreasing absorption capacity of vocational education graduates indicates barriers to teaching quality. This Research aims to analyze the factors that influence the quality of vocational learning. Method: This Research uses quantitative methods. The sample is aircraft maintenance engineering students at Aviation Polytechnic. Data analysis uses the Structural Equation Model-Partial Least Square. Result: Validation of the research instrument resulted in the loading factor, AVE, Cronbach Alfa, and SRMR meeting the requirements, so the instrument and variables were declared valid and reliable, and the model was declared fit. Lecturer behavior and the quality of learning and learning resources have a direct and significant positive relationship. Meanwhile, management support through learning resources has influenced the quality of learning by 51.0%. Novelty: The quality of learning in vocational education is influenced by the role of lecturer behavior and management support in providing and managing quality learning resources. The collaboration of those three aspects can improve the quality of competency of vocational education graduates. The high competency of aviation vocational education graduates can increase the absorption capacity of graduates in the era of Revolution 4.0.